Retrospective review of the management of acute infections and the indications for antibiotic prescription in primary care in northern Thailand. Issue 7 (30th July 2018) - Greer, Rachel C; Intralawan, Daranee; Mukaka, Mavuto; Wannapinij, Prapass; Day, Nicholas P J; Nedsuwan, Supalert; Lubell, Yoel
Abstract : Introduction: Antibiotic use in low-income and middle-income countries continues to rise despite the knowledge that antibiotic overuse can lead to antimicrobial resistance. There is a paucity of detailed data on the use of antibiotics in primary care in low-resource settings. Objective: To describe the presentation of acute infections and the indications for antibiotic prescription. Design: A 2-year retrospective review of routinely collected data. Setting: All 32 primary care units in one district in northern Thailand. Participants: Patients attending primary care with a history of fever, documented temperature, International Statistical Classification of Diseases 10 code for infection or prescribed a systemic antibiotic. Patients attending after the initiation of a study on C-reactive protein testing in four centres were excluded. Outcome measures: The proportion of patients prescribed an antibiotic and the frequency of clinical presentations. Results: 762 868 patients attended the health centres, of whom 103 196 met the inclusion criteria, 5966 were excluded resulting in 97 230 attendances consisting of 83 661 illness episodes. 46.9% (39 242) of the patients were prescribed an antibiotic during their illness. Indications for antibiotic prescription in the multivariable logistic regression analysis included male sex (adjusted OR (aOR) 1.21 (95% CI 1.16 to 1.28), p<0.001), adults (aOR 1.77 (95% CI 1.57 to 2), p<0.001) and a temperature >37.5°C (aOR 1.24 (95% CI 1.03 to 1.48), p=0.020). 77.9% of the presentations were for respiratory-related problems, of which 98.6% were upper respiratory tract infections. The leading infection diagnoses were common cold (50%), acute pharyngitis (18.9%) and acute tonsillitis (5%) which were prescribed antibiotics in 10.5%, 88.7% and 87.1% of cases, respectively. Amoxicillin was the most commonly prescribed antibiotic. Conclusions: Nearly half of the patients received an antibiotic, the majority of whom had a respiratory infection. The results can be used to plan interventions to improve the rational use of antibiotics. Further studies in private facilities, pharmacies and dental clinics are required.